Entwicklung, Struktur und räumliche Differenzierung des Fremdenverkehrs der Balearen - Riedel, Uwe (ERDKUNDE, 1972)
With almost 1,5 million tourists and over 16 million tourist bednights (in 1967), the Balearic Islands stand first in importance among the tourist regions of Spain. The tourist season is marked by a pronounced peak in the summer months. The main share in this flood of tourists is taken by the British (with more than 30% of all tourists) followed by Germans (19,1%) and Spanish visitors (13,3%). Up till now almost 90% of all visitors have chosen the island of Mallorca and over 9% the island of Ibiza as their holiday destination; Menorca and Formentera, on the other hand, are still largely off the beaten track for mass tourism. The core and goal of this investigation is to illuminate the spatial differentiation of tourism on the Balearic Islands. A catalogue of indicators is drawn upon to characterise the nature of tourism in the individual communes, a catalogue which has been considerably expanded in comparison to similar methodological investigations: tourist density, tourist intensity (by different methods of calculation), relative tourist capacity and intensity of utilisation of capacity. Only by combining the criteria here applied in a systematic way is it possible to gauge the real importance of tourism for a commune. Using this method, only five communes in the archipelago can be classified as ’tourist communes’.